Obesity is correlated with poor outcome after allogeneic hematopoietic stem cell transplantation in patients with acute leukemia. (27th May 2020) - Yu, Jian; Lin, Shangnao; Luo, Yi; Shi, Jimin; Tan, Yamin; Lai, Xiaoyu; Zhao, Yanmin; Ye, Yishan; Zhu, Yuanyuan; Zheng, Weiyan; Huang, He
Abstract: Objective: The relationship between body mass index and overall survival has been controversial in patients who suffered from hematological malignancies and underwent hematopoietic stem cell transplantation. Methods: We collected the data of 686 acute leukemia patients who received only one allogeneic hematopoietic stem cell transplantation in our center from 2008 to 2017. Patients were divided into four groups (underweight, normal weight, overweight and obesity) according to their body mass index pre-hematopoietic stem cell transplantation. Results: 56.4% of patients had normal body mass indices, 17.3% were underweight, 20.4% were overweight and 5.8% were with obesity. Concerning long-term follow-up, the probability of overall survival was significantly lower in overweight ( P = 0.010) and patients with obesity ( P = 0.065) as compared with normal weight patients, and no statistically significant difference between underweight and normal weight individuals ( P = 0.810). The results demonstrated that higher body mass index was associated with poorer overall survival (hazard ratio: 1.79; 95% confidence interval: 1.33–2.40, P < 0.001) and shorter leukemia-free survival (hazard ratio: 1.78; 95% confidence interval: 1.35–2.34, P < 0.001). Additionally, patients exhibiting a higher body mass index were more likely to face the problem of relapse (30.6 vs 20.9%, P < 0.001). Furthermore, non-relapse mortality of patients with obesity was statistically higher than normal weight patients (22.5 vs 9.6%, P = 0.027). Besides, individuals with a higher abdominal girth had shorter survival (hazard ratio: 1.73; 95% confidence interval: 1.29–2.31, P < 0.001) and higher relapse rate (hazard ratio: 1.78; 95% confidence interval: 1.29–2.45, P = 0.001) as compared with those with a lower abdominal girth. Conclusion: Our results indicate that obesity at pre-hematopoietic stem cell transplantation stage, whether characterized by higher body mass index or abdominal girth, is correlated with poorer outcome. Abstract : The study enrolled 686 acute leukemia patients underwent allogeneic hematopoietic stem cell transplantation. The results indicated that obesity at pre-hematopoietic stem cell transplantation stage is correlated with poorer outcome.